+0  
 
0
44
2
avatar

If h(z)=2z^2-5z+7, find h(3c)

Guest Mar 5, 2017
edited by Guest  Mar 5, 2017
Sort: 

2+0 Answers

 #1
avatar+4157 
+1

h(z) = 2z- 5z + 7

 

To find h(3c), replace each z with 3c.

h(3c) = 2(3c)2 - 5(3c) + 7

 

Now just simplify.

h(3c) = 2(9c2) - 5(3c) + 7

 

h(3c) = 18c2 - 15c + 7

hectictar  Mar 5, 2017
 #2
avatar
+5

Ohhhh ok thanks! That cleared it up I did the second step wrong

Guest Mar 5, 2017

3 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details